Nutrient indexing and land use cum fertility mapping of temperate farm soils of Bhaderwah in NW Himalayas, India - CHAUDHARY, SANJEEV KUMAR; KOTWAL, NEERAJ; KUMAR, MANOJ; SHARMA, NIRMAL; SHARMA, ROHIT; CHARAK, AMIT SINGH; CHAUHAN, DEVENDRA KUMAR; KUMAR, VIJAY (Journal of Soil and Water Conservation, 2025)
Nutrient indexing and fertility mapping of Sartangal farm soils of Regional Horticultural Research Sub Station of SKUAST-Jammu (J&K) was carried out. Representative soil samples drawn from different land uses were analysed for important physico-chemical characteristics and available nutrients. These soils were sandy loam to sandy clay loam in texture, strongly to moderately acidic in pH with normal electrical conductivity (EC) and high to very high organic carbon (OC) content. As per nutrient index (NI) values, these soils fell in high category of available N, P, Mn, Fe, Cu and B; medium category of available K and S; and low category of available Zn. Regression analysis indicated about 99 and 19% contribution of OC towards total variability in available N and Cu, respectively. About 35 and 33% variability in available P and S, in order, could be attributed to pH and EC together; while 32 and nearly 45% of that in available S and Cu, in order, could be attributed to OC and EC together. EC alone could explain about 34, 75, 22, 42, 57, 16 and 60% of total variability in available P, K, S, Mn, Zn, Cu and B, respectively. On the basis of data generated, land use-cum-soil fertility map of the study area was prepared.